20. Habituation of somatosensory evoked potentials in dystonia. Issue 12 (December 2016) - Cardillo, A.; Gorini, M.; Alibardi, A.; Greco, D.; Rinalduzzi, S.; Pierelli, F.; Fattapposta, F.; Marinelli, L.; Currà, A.
Abstract : Dystonia is a disorder of both motor and sensory function, clinically characterized by involuntary movements, abnormal postures, and abnormal sensory discrimination. Whereas most data on the physiology of motor cortices are consistent with a general frame of reduced inhibition and maladaptative plasticity, electrophysiological data in sensory cortices are controversial. Habituation refers to response decrement with repeated stimulation, and reflects mechanisms that alter synaptic effectiveness in the stimulated cortex through LTD or LTP-like phenomena. We investigated somatosensory evoked potentials (SEPs) habituation in patients with dystonia and hemifacial spasm (HSF). We recorded median-nerve SEPs in 28 patients (8 cranial, 4 cervical, 1 cranial-cervical dystonia, 15 HSF) and 18 age-matched controls. We measured N20-P25 amplitudes from 3 blocks of 200 sweeps, and assessed amplitude of block 1, and habituation from amplitude changes between the 3 sequential blocks. ANOVA showed a main effect of factor group ( F = 4.4 p = 0.015). In patients with dystonia, SEP amplitudes were normal in block 1, but thereafter failed to habituate ( p = 0.03). Patients with hemifacial spasm had normal SEP amplitudes and habituation ( p = 0.98). SEP habituation is altered in dystonia indicating that somatosensory cortex becomes hyperresponsive. This abnormality is not the result of involuntary movements because in patients with HSF SEPs habituate normally.